2022
DOI: 10.1371/journal.pone.0267822
|View full text |Cite
|
Sign up to set email alerts
|

Operational challenges and considerations for COVID-19 research in humanitarian settings: A qualitative study of a project in Eastern Democratic Republic of the Congo and South Sudan

Abstract: Since the beginning of the COVID-19 pandemic, much research has been conducted globally, but relatively few studies have been carried out in complex emergency settings that pose numerous operational challenges. We conducted a qualitative study to explore the barriers and enablers of a COVID-19 cohort study conducted in South Sudan and Eastern Democratic Republic of the Congo, to inform future research on COVID-19 and infectious diseases in humanitarian settings. We used a case study design embedded within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This cohort study details clinical progression and outcomes of 144 hospitalized COVID-19 patients in North and South Kivu in eastern DRC and Juba, SSD. The observed hospital mortality proportion of 16.7% is comparable to findings from global systematic reviews of COVID-19 inpatient survival [16,17] but lower than prior studies in DRC which observed mortality rates of 22% and 32% and were conducted earlier in the pandemic in Kinshasa [18,19]. However, actual mortality in study facilities was higher due to the inability to enroll patients presenting near death; this figure was not tracked in SSD, however in DRC 24 patients died before being admitted to the study (2.3% of DRC study participants).…”
Section: Discussionsupporting
confidence: 69%
“…This cohort study details clinical progression and outcomes of 144 hospitalized COVID-19 patients in North and South Kivu in eastern DRC and Juba, SSD. The observed hospital mortality proportion of 16.7% is comparable to findings from global systematic reviews of COVID-19 inpatient survival [16,17] but lower than prior studies in DRC which observed mortality rates of 22% and 32% and were conducted earlier in the pandemic in Kinshasa [18,19]. However, actual mortality in study facilities was higher due to the inability to enroll patients presenting near death; this figure was not tracked in SSD, however in DRC 24 patients died before being admitted to the study (2.3% of DRC study participants).…”
Section: Discussionsupporting
confidence: 69%
“…A potential limitation of our study is that the findings from our study are from a single urban national referral hospital and some contextual factors may not be generalizable in different settings. However, many such centers in Uganda and other sub-Saharan African countries often have similar challenges [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemics, particularly the very recent coronavirus (SARS-CoV-2, hereafter COVID-19) pandemic, most of the services provided by the companies, organizations and governments' facilities have been affected significantly in terms of quality and quantity [1][2][3][4][5][6]. On one hand, most of the employees have been at risk of infection and on the other hand, the work-flows and functions have become slow.…”
Section: Introductionmentioning
confidence: 99%